2022
DOI: 10.1002/advs.202201341
|View full text |Cite
|
Sign up to set email alerts
|

Light‐Fueled Submarine‐Like Droplet

Abstract: Flexibly and precisely manipulating 3D droplet transportation is a fundamental challenge for broad implications in diagnostics, drug delivery, bioengineering, etc. Herein, a light method is developed for manipulating a droplet to make it behave like a submarine. This light method enables flexible 3D transportation, stable suspension, and floating of a droplet, which can be freely altered. It is demonstrated that the localized photothermal effect induced thermocapillary flow in the water droplet/oil phase is re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…When the cooling rate is less than 0.5 °C/min, no microdroplet injection was observed (Figure S4b). Note that the Marangoni force is commonly considered the driving force for the self-propulsion of droplets in immiscible liquids. ,, However, in this work, the Marangoni force mainly contributes to the injection process, and the motion of LC droplets during the rapid cooling is rarely observed. Although the concrete mechanism requires further study, we found that rapid cooling is vital to injection rather than propulsion, avoiding the formation of steady interior conventions within liquid droplets that would lead to droplet motion.…”
Section: Resultsmentioning
confidence: 92%
“…When the cooling rate is less than 0.5 °C/min, no microdroplet injection was observed (Figure S4b). Note that the Marangoni force is commonly considered the driving force for the self-propulsion of droplets in immiscible liquids. ,, However, in this work, the Marangoni force mainly contributes to the injection process, and the motion of LC droplets during the rapid cooling is rarely observed. Although the concrete mechanism requires further study, we found that rapid cooling is vital to injection rather than propulsion, avoiding the formation of steady interior conventions within liquid droplets that would lead to droplet motion.…”
Section: Resultsmentioning
confidence: 92%
“…Light-based transportation of floating droplets may also be achieved via Marangoni flows induced by localized photothermal effects. The method expands to 3D transportation in an oil bath offering flexible control of submarine-like droplets (Figure A) . To manipulate droplets on a solid–liquid interface, Liu et al created a directional anchoring liquid-infused superamphiphobic surface via ultrafast laser-based technology .…”
Section: Droplet Microfluidicsmentioning
confidence: 99%
“…Droplet manipulation techniques. (A) 3D light control of submarine-like droplets by using Marangoni flows induced by localized heating (ref ). Adapted from Light-Fueled Submarine-Like Droplet, Yang, Y.; Chen, R.; Zhu, X.; Ye, D.; Yang, Y.; Li, W.; Li, D.; Li, H.; Liao, Q. Adv.…”
Section: Droplet Microfluidicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, all droplet arrays were connected with the oil pool, resulting in the threat of cross-contamination and the compatibility of droplet manipulation methods. [33][34][35][36][37] On the lubricated slippery surfaces, a homogeneous film of lubricant is locked in the micro/nanoporous structures on the substrate. [38,39] The oil cloaking could significantly prevent water evaporation with a positive spreading coefficient, but the high-throughput droplet arrays were hardly created.…”
Section: Introductionmentioning
confidence: 99%